2019
DOI: 10.1161/strokeaha.118.022912
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Susceptibility Vessel Sign for Arterial Recanalization and Clinical Improvement in Ischemic Stroke

Abstract: Background and Purpose— Our goal was to evaluate whether the presence of a low signal intensity known as susceptibility vessel sign (SVS) on T2*-gradient echo imaging sequence was predictive of arterial recanalization and the early clinical improvement after mechanical thrombectomy. Methods— This observational study was based on a prospective database of acute ischemic strokes treated by mechanical thrombectomy. Inclusion criteria were patients with acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 9 publications
2
48
0
Order By: Relevance
“…In previous reports, more proximal occlusions, such as those in the internal carotid artery (ICA) and M1 segment of the middle cerebral artery (MCA), was associated with successful recanalization [5, 6]. Other studies have revealed that an erythrocyte-rich thrombus, appearing as a hyperdense signal on computed tomography or a low-intensity signal (known as a susceptibility vessel sign) on T2*gradient echo magnetic resonance imaging, predicts successful recanalization [7, 8, 9]. Conversely, difficult anatomical access [10, 11] and intracranial atherosclerotic stenosis [9, 12] have been reported to be associated with unsuccessful recanalization.…”
Section: Introductionmentioning
confidence: 99%
“…In previous reports, more proximal occlusions, such as those in the internal carotid artery (ICA) and M1 segment of the middle cerebral artery (MCA), was associated with successful recanalization [5, 6]. Other studies have revealed that an erythrocyte-rich thrombus, appearing as a hyperdense signal on computed tomography or a low-intensity signal (known as a susceptibility vessel sign) on T2*gradient echo magnetic resonance imaging, predicts successful recanalization [7, 8, 9]. Conversely, difficult anatomical access [10, 11] and intracranial atherosclerotic stenosis [9, 12] have been reported to be associated with unsuccessful recanalization.…”
Section: Introductionmentioning
confidence: 99%
“…There were no differences between S-SVS and A-SVS with respect to patient age [72 (IQR, 63-79) vs. 67 (IQR, 55-76), p = 0.960], female sex (52 vs. 54%, p = 1.000), baseline NIHSS [14 (IQR, 10-20) vs. 17 (IQR, [13][14][15][16][17][18][19][20][21][22], p = 0.12], or frequency of left sided occlusions (71 vs. 54%, p = 0.19), respectively (Table 1). A-SVS clots were significantly longer compared to S-SVS clots [19 mm (IQR,[15][16][17][18][19][20][21][22][23][24] vs. 8 mm (IQR, 10-15), p = 0.0002] (Table 2). There were no other significant differences between the two groups with regard to neuroimaging variables, which included core infarction volume, penumbra volume, and HIR collateral robustness (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies have used SVS identified on gradient-echo imaging (T2 * ) ( 21 ) to detect ( 5 ), localize ( 22 ), and measure clot length ( 5 , 22 ) without contrast administration. Whether SVS is a predictor of reperfusion after MT remains controversial ( 9 , 23 ). Our findings support the hypothesis that SVS is a biomarker of reperfusion when thrombus morphology is considered.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 22 studies presented a relationship between SVS/PHVS, recanalization status and / or clinical outcomes in patients with acute ischaemic stroke (AIS). Of the 22 studies, 7 studies were further excluded from qualitative analysis due to either inadequate data 19 27 28, using different definition of SVS 29, non-standardized definition of recanalization 4 30 or mRS was evaluated at 6 months 31 (see Supplementary Table 1 ). No studies were considered to be seriously flawed as per the QUADAS-2.…”
Section: Resultsmentioning
confidence: 99%